(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Upper gastrointestinal (UGI) endoscopy is a safe and sensitive investigation in the diagnosis of upper gastrointestinal diseases. There is limited study on paediatric upper GI endoscopy in our country. This study was done only in BSMMU, a tertiary care health facility of Bangladesh. Objectives: The aim of the study was to find out the indications, common endoscopic findings and immediate post procedure complication of UGI endoscopy in children. Methods: This is a retrospective analysis of 100 patients from August 2013 to October 2014. The indications for UGI endoscopy, common endoscopic findings and immediate post procedure complications were collected from case recording &were analyzed. Results: The commonest indication was upper GI bleeding in the form of hematemesis with or without melenae (41%). The most common finding was esophageal varices (49%). Less common findings were esophagitis, gastritis & gastro-duodenal ulcer. There was no post procedure complication. Conclusion: In the study, the commonest indication for Pediatric UGI endoscopy was upper GI bleeding and the commonest endoscopic abnormality was esophageal varices. No immediate post procedure complication was noted in the study. Bangladesh J Child Health 2016; VOL 40 (1) :17-20